2005
DOI: 10.1111/j.1600-0609.2005.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing new drugs for the treatment of lymphoma

Abstract: Despite the great progress that has been made over the last several decades in the treatment of lymphoma, the prognosis for patients with relapsed disease, and particular sub‐types of lymphoma like mantle cell and T cell lymphoma, remains quite poor. While major advances in the use of combination chemotherapy, monoclonal antibodies, peripheral blood stem cell transplants, and radioimmunotherapy, have provided new opportunities to alter the natural history of these diseases, and even improve cure rates among el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…10 Vorinostat (Zolinza [Merck, Whitehouse Station, NJ], suberoylanilide hydroxamic acid, SAHA) is an orally bioavailable inhibitor 11 of class I and II HDACs. 12 In preclinical studies, vorinostat has been shown to cause accumulation of acetylated histones and to induce cell-cycle arrest and apoptosis in a broad range of cancer cell lines, including CTCL lines. 12,13 Vorinostat also showed antitumor activity at in leukemia, lymphoma, and solid-tumor models in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Vorinostat (Zolinza [Merck, Whitehouse Station, NJ], suberoylanilide hydroxamic acid, SAHA) is an orally bioavailable inhibitor 11 of class I and II HDACs. 12 In preclinical studies, vorinostat has been shown to cause accumulation of acetylated histones and to induce cell-cycle arrest and apoptosis in a broad range of cancer cell lines, including CTCL lines. 12,13 Vorinostat also showed antitumor activity at in leukemia, lymphoma, and solid-tumor models in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…12 In preclinical studies, vorinostat has been shown to cause accumulation of acetylated histones and to induce cell-cycle arrest and apoptosis in a broad range of cancer cell lines, including CTCL lines. 12,13 Vorinostat also showed antitumor activity at in leukemia, lymphoma, and solid-tumor models in vivo. [14][15][16][17][18] Phase 1 trials to evaluate the safety and activity of vorinostat were conducted in patients with advanced solid and hematologic malignancies, including CTCLs.…”
Section: Introductionmentioning
confidence: 99%
“…In leukemias, HDACs have been linked to the activity of translocated oncoproteins and the suppression of gene expression necessary for normal differentiation (54). Suberoylanilide hydroxamic acid (SAHA) and the cyclic peptide, depsipeptide (FR‐901228), belong to the group of histone deacetylase inhibitors (55). They present challenging therapeutic compounds for patients with both solid tumors and (extra)nodal lymphomas.…”
Section: The Art Of Treating – the Call Is On Pathogenesismentioning
confidence: 99%
“…Since NF-κB plays a central role in the regulation of various gene expression involved in cell survival, apoptosis, carcinogenesis, and infl ammation, this molecule has been regarded as a very potential therapeutic target for many cancers (Baud and Karin, 2009). Bortezomib, a tripeptide with pyrazinoic acid, phenylalanine, and leucine with boronic acid, is a proteasome inhibitor that hinders activation of NF-κB by inhibiting cytoplasmic IκBα degradation (O'Connor, 2005). In preclinical studies, it inhibited proliferation of HL cell lines, and induced cell cycle arrest as well as apoptosis (Adams, 2003;Zheng et al, 2004).…”
Section: Hrs Cellsmentioning
confidence: 99%